1994
DOI: 10.1007/bf02184161
|View full text |Cite
|
Sign up to set email alerts
|

Strongly exciton-coupled BChle chromophore system in the chlorosomal antenna of intact cells of the green bacteriumChlorobium phaeovibrioides: A spectral hole burning study

Abstract: Spectral hole burning studies of intact cells of the green bacteriumChlorobium phaeovibrioides have proven that the Qy-absorption system of antenna bacteriochlorophylle (BChle) should be interpreted in terms of the delocalized exciton level structure of an aggregate. For the first time the 0-0 band of the lowest exciton state of BChle aggregates has been directly detected as the lowest energy inhomogeneously broadened band (FWHM ∼ 100 cm(-1); position of maximum, at ∼ 739 nm) of the near-infrared BChle band in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…The chlorosome pigments should be distinguished from ideal J-aggregates where the J-band with the largest oscillator strength is also the lowest exciton state (LES) [23,43]. Pšenčík et al [23] has shown that LESs in chlorosomes from C. tepidum are distributed within 760-800 nm range, while the absorption maximum is at 750 nm.…”
Section: A Spectral Densitiesmentioning
confidence: 99%
“…The chlorosome pigments should be distinguished from ideal J-aggregates where the J-band with the largest oscillator strength is also the lowest exciton state (LES) [23,43]. Pšenčík et al [23] has shown that LESs in chlorosomes from C. tepidum are distributed within 760-800 nm range, while the absorption maximum is at 750 nm.…”
Section: A Spectral Densitiesmentioning
confidence: 99%
“…lA). The Hamiltonian can be written as (13) + ~ ~ We consider low-temperature optical spectra assuming a weak exclton-phonon coupling (3)(4)(5). In this case the perturbation theory for…”
Section: Theorymentioning
confidence: 99%
“…One of the structural optlmizlng factors is oligomerization of antenna pigments [2). The chlorosome of green bacteria contalning several thousands of antenna bacteriochlorophyll (BChl) c,d or e molecules in an aggregated state is the most convincing example of natural antenna of oligomeric type (3)(4)(5). The discovered strong orientational ordering of the near-infrared transition dipoles of BChl c in situ (6) suggested that an elementary BChl aggregate has the form of a linear chain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations